Somatosensory control of spinal reflex circuitry during robotic-assisted stepping - Tsuyoshi Nakajima; Kiyotaka Kamibayashi; Kimitaka Nakazawa (Japanese Society of Physical Fitness and Sports Medicine, 2012)
Spinal reflexes are known to be strongly modulated in a phase- and task dependent manner during walking in both humans and cats. However it is not clear whether afferent feedback from the leg plays a more important role in regulating this modulation in the leg and arm muscles. This short review mainly describes the recent findings concerning the effect of somatosensory inputs on the excitability of cutaneous reflex and H-reflex pathways during robotic-assisted stepping. The experimental results are discussed with recent advances in the field of human motor control, and the implications of locomotor rehabilitation for individuals with spinal cord injury are discussed as well.